2006
DOI: 10.3201/eid1204.051379
|View full text |Cite
|
Sign up to set email alerts
|

Lineage 1 and 2 Strains of Encephalitic West Nile Virus, Central Europe

Abstract: An encephalitic lineage 2 strain of WNV is observed for the first time outside Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
370
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 406 publications
(381 citation statements)
references
References 26 publications
6
370
0
5
Order By: Relevance
“…The virus isolated was WNV lineage 2, homologous to the strains previously found in Hungary. 3 Recently, in August 2010, a WNV outbreak was detected in Central Macedonia (Northern Greece) with an unexpected lethality in humans; the sequences obtained were more than 99% similar to the WNV lineage 2 found in Hungary and Austria in recent years (ProMED-mail, archive no. 20100914.3312).…”
Section: Introductionmentioning
confidence: 99%
“…The virus isolated was WNV lineage 2, homologous to the strains previously found in Hungary. 3 Recently, in August 2010, a WNV outbreak was detected in Central Macedonia (Northern Greece) with an unexpected lethality in humans; the sequences obtained were more than 99% similar to the WNV lineage 2 found in Hungary and Austria in recent years (ProMED-mail, archive no. 20100914.3312).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, those WNV sequences falling outside KUNV were not themselves a monophyletic group; rather there were three separate lineages each supported by a highly significant internal branch (Figure 1). Bakonyi et al (2006) showed a similar topology in a phylogeny using a smaller number of sequences. Building on earlier analyses (Lanciotti et al 1999(Lanciotti et al , 2003, Bakonyi et al (2006) proposed five separate lineages in the WNV phylogeny as follows: (1) the WNV sequences clustering with KUNV constitute lineage 1a; (2) KUNV itself constitutes lineage 1b; (3) lineage 2 is the group including AY688948 (Israel); DQ116961 (Hungary); DQ318019 (Senegal), and DQ318020 (Central African Republic); (4) lineage 3 is represented by AY765264 (Czech Republic); and (5) lineage 4 is represented by AY277251 (Russia).…”
Section: Phylogenetic Analysesmentioning
confidence: 73%
“…Phylogenetic analyses by various methods supported the five lineages of West Nile virus (WNV) proposed by Bakonyi et al (2006), one of which corresponds to Kunjin virus (KUNV). Thus, WNV as currently defined, is paraphyletic.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations